Detection of hepatic steatosis using the controlled attenuation parameter: a comparative study with liver biopsy - ÇELİKEL, ÇİĞDEM; ERGELEN, RABİA; YILMAZ, YUSUF (TAYLOR & FRANCIS LTD, 2014)
Objective. Measurements of controlled attenuation parameter (CAP) with transient elastography (FibroScan (R); EcoSens SA, Paris, France) may provide an accurate noninvasive assessment of hepatic steatosis. Herein, we prospectively determined the accuracy of liver fat quantification with CAP values in patients with chronic liver diseases and compare the results with those of histological assessment of steatosis as reference standard. Materials and methods. We enrolled 50 Turkish patients with various forms of chronic liver diseases. All patients underwent both CAP assessment and ultrasonography-guided liver biopsy. Results. On liver biopsy, 16 (32%) patients had S0, 12 (24%) had S1, 9 (18%) had S2, and 13 (26%) had S3. The CAP values increased significantly (p < 0.001) for each steatosis stage on liver biopsy: S0, 222 dB/m; S1, 250 dB/m; S2, 270 dB/m; and S3, 318 dB/m. A cutoff value of 257 dB/m could distinguish significant steatosis (S2-S3) from S0 (Sn 89%, Sp 83%, positive likelihood ratio 5.33, negative likelihood ratio 0.13, AUROC = 0.93). Multivariable analysis indicated that neither liver fibrosis (p = 0.58) nor disease etiology (p = 0.96) had a significant impact on the association between CAP and the stage of steatosis. Conclusion. The determination of CAP using transient elastography can represent an important step forward toward the goal of an imaging liver biopsy.
Keywords: controlled attenuation parameter; fibroscan; hepatic steatosis; nonalcoholic fatty liver disease; DENSITY FAT FRACTION; NONINVASIVE ASSESSMENT; NONALCOHOLIC STEATOHEPATITIS; IMAGING TECHNIQUES; DISEASE; CAP; DIAGNOSIS; QUANTIFICATION; VALIDATION; MECHANISMS